Impact of Dietary Coconut Oil (Cocos nucifera L.) on Aeromonas hydrophila Colonization and Lactic Acid Bacteria Populations in Zebrafish (Danio rerio): Implications for Aquaculture Health - Qosimah, Dahliatul; Iwanegbe, Izuwa; Efendi, Achmad; Nasution, Angellica Christine; Hardiana, Ameilia; Zahrany, Naura Nisrina; Satria Putra, Pramadhita Wika; Daniswara, Respati Satya (CV. Komunitas Dunia Peternakan, 2025)
The Aeromonas hydrophila (A. hydrophila) Aeromonas hydrophila (A. hydrophila) is an opportunistic pathogen causing significant losses in aquaculture. The overuse of antibiotics has led to antimicrobial resistance, necessitating alternative control strategies. This study evaluates the potential of coconut oil to inhibit A. hydrophila colonization in gills, brain, and gut microbiota of zebrafish while enhancing lactic acid bacteria (LAB) populations. A completely randomized design was used with five groups: a negative control (healthy), a positive control (A. hydrophila-infected), and three treatment groups (1000 mg/kg, 2000 mg/kg, 4000 mg/kg coconut oil) for 60 days. Bacterial load in gills and brain was quantified using the pour plate method on Rimler-Shotts agar, while LAB in the gut was assessed using de Man, Rogosa, and Sharpe Agar (MRSA). 1000 mg/kg coconut oil significantly reduced A. hydrophila in the gills (0.3 ± 0.09 × 10⁷ CFU/ml) compared to the positive control (138.13 ± 11.26 × 10⁷ CFU/ml). 4000 mg/kg was most effective in reducing A. hydrophila in the brain (1.78 ± 0.51 × 10⁷ CFU/ml vs. 4.53 ± 0.40 × 10⁷ CFU/ml in the positive control). LAB populations significantly increased (p < 0.0001), with the highest count at 1000 mg/kg (9.20 ± 0.87 × 10⁷ CFU/ml), followed by 2000 mg/kg (3.16 ± 0.13 × 10⁷ CFU/ml), and 4000 mg/kg (1.78 ± 0.35 × 10⁷ CFU/ml). Coconut oil effectively enhances LAB populations, inhibits A. hydrophila colonization, and acts as a natural antimicrobial and probiotic agent. The 1000 mg/kg dose is optimal for gut microbiota improvement, while 4000 mg/kg protects brain tissues, highlighting coconut oil’s potential as an eco-friendly alternative to antibiotics in aquaculture.